2017
DOI: 10.1080/21622965.2017.1384924
|View full text |Cite
|
Sign up to set email alerts
|

Memory and linguistic/executive functions of children with borderline intellectual functioning

Abstract: Children with Borderline Intellectual Functioning (BIF) have received a minimal amount of research attention and have been studied in conjunction with Intellectual and Developmental Disabilities. The present study intends to broaden the knowledge of BIF, by analyzing domains such as verbal memory and visual memory, as well as tasks that rely simultaneously on memory, executive functions, and language. A cross-sectional, comparison study was carried out between a group of 40 children with BIF (mean age = 10.03;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(86 reference statements)
0
3
0
2
Order By: Relevance
“…The main characteristics of borderline intelligent children include poor working memory and executive functioning, problems with knowledge organization, difficulties with generalization, poor attention, difficulties with verbal expression and listening, lack of motivation to learn, and behavioral deficits [28][29][30]. Previous studies have examined the impact of cognitive functions such as working memory and executive functioning on academic achievement in specific domains such as reading or compared profiles on the subtests of the WISC among groups of borderline intelligent children, children with learning disabilities, intellectual disabilities, and typical developing children [31,32], and teachers have found it challenging to identify slow learners in the classroom outside of intelligence tests. The WISC-IV is the most commonly used standardized test to assess intelligence in children aged 6 to 16 [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of borderline intelligent children include poor working memory and executive functioning, problems with knowledge organization, difficulties with generalization, poor attention, difficulties with verbal expression and listening, lack of motivation to learn, and behavioral deficits [28][29][30]. Previous studies have examined the impact of cognitive functions such as working memory and executive functioning on academic achievement in specific domains such as reading or compared profiles on the subtests of the WISC among groups of borderline intelligent children, children with learning disabilities, intellectual disabilities, and typical developing children [31,32], and teachers have found it challenging to identify slow learners in the classroom outside of intelligence tests. The WISC-IV is the most commonly used standardized test to assess intelligence in children aged 6 to 16 [25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have reported that children with BIF have impaired working memory compared to typically de-veloping children [37,38]. In other words, slow learners showed lower verbal and visuospatial short-term and working memory performance than typically developing children matched for chronological age.…”
Section: Discussionmentioning
confidence: 99%
“…In children and adolescents with BIF, total cognition, verbal and visual performance, processing speed, and working memory decline over time [ 10 ]. Children with BIF show deficits in visual performance, short-term and long-term memory, working memory capacity, and processing speed and seem unable to catch up with the increasing demands in various domains as they grow older [ 10 - 14 ]. Children with BIF perform worse than their normal peers in more complex cognitive domains, including executive functions, abstract reasoning, selective and sustained attention, and perceptual organization [ 10 , 12 , 15 ].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Têm sido realizadas numerosas investigações, com a BANC, junto de crianças e adolescentes com desenvolvimento típico (Albuquerque, 2012;Albuquerque et al, 2010;Coutada & Albuquerque, 2018;Moura et al, 2013;Simões et al, 2007Simões et al, , 2011, com perturbações do neurodesenvolvimento (e.g., dislexia, perturbação de hiperatividade/défice de atenção, perturbação do desenvolvimento intelectual, perturbação da linguagem) (Coelho et al, 2013;Dias et al, 2019;Moura et al, 2014Moura et al, , 2017Moura, et al, 2015), com lesões ou disfunções cerebrais (e.g., traumatismo crânioencefálico, epilepsia) (A. F. Lopes et al, 2010Santos, 2006), com perturbações do comportamento (e.g., perturbação desafiante de oposição) (Sá et al, 2008), com problemas escolares (e.g., dificuldades de aprendizagem, sobredotação) (Cardoso, 2007;Pereira et al, 2006Pereira et al, , 2016 ou com risco social (e.g., vítimas de maus tratos, institucionalizados) (Correia, 2013;Ferreira, 2009) possibilitando, deste modo, a identificação de perfis neurocognitivos específicos que auxiliam no diagnóstico e intervenção.…”
Section: Introductionunclassified
“…As dificuldades são mais acentuadas na memória, nas funções executivas, na atenção e na velocidade de processamento (A. F. Lopes et al, 2010. A capacidade discriminante das pontuações da BANC tem sido igualmente observada na perturbação do espectro do autismo (Mouga et al, 2021), no funcionamento intelectual borderline (Dias et al, 2019), na perturbação específica da linguagem (Coelho et al, 2013), na perturbação desafiante de oposição (Sá et al, 2008), entre outras.…”
Section: Introductionunclassified